Palatability of tropical forage legumes - Souto, Sebastião Manhães; Lima, Carlos Rodrigues; Lucas, Enésio Delgado de (Pesquisa Agropecuaria Brasileira, 2014)
The palatability of five tropical forage legumes, Stylosanthes guianensis cv 1022, Macropitilium atropurpureum cv Siratro, Pueraria phaseoloides cv Deodoro, Centrosema pubescens cv Deodoro and Glycine wightii cv IRI n.° 1, was studied in an experiment conducted at the Institute of Agricultural Research (South-Central) IPEACS, at Itaguaí, RJ. Animals used were of mixed Zebu x Holstein lineage and the experimental design was made in randomized blocks with one legume per treatment in four replications (cafeteria style), during four experimental period. The time periods of grazing and the consumption of each type of forage were the two methods used to measure the palatability of the legumes studied in this experiment. In the first experimental period, during July 1970, the productivity of Stylosanthes guianensis and Macropitilium atropurpureum was not significantly different, but Stylosanthes was superior to the other legumes studied viz. Pueraria phaseoloides, Centrosema pubescens and Glycine wightii. According to the cafeteria trial, the two animals spent significantly more time on Stylosanthes and Siratro than the other legumes. The consumption of forage by the animals was highest for Stylosanthes but not significantly different from any the other legumes except G. wightii. In the second period, August-September 1970, no statistical differences were observed among the legumes. However, in the third period, October 1970, Stylosanthes was not significantly different from Siratro but had a higher yield and palatability than the others three legumes. In the fourth period. March-April 1971. Stylosanthes produced significantly much more than the other four legumes but the lower consumption was not statistically different. There were no statistical differences among the replications for all the observations in the four experimental periods.
Keywords: Stylosanthes guianensis; Macropitilium atropurpureum cv Siratro; Pueraria phaseoloides; Centrosema pubescens; Glycine wightii